Differential ACPA Binding to Nuclear Antigens Reveals a PAD-Independent Pathway and a Distinct Subset of Acetylation Cross-Reactive Autoantibodies in Rheumatoid Arthritis - Lloyd, Katy A.; Wigerblad, Gustaf; Sahlström, Peter; Garimella, Manasa G.; Chemin, Karine; Steen, Johanna; Titcombe, Philip J.; Marklein, Bianka; Zhou, Diana; Stålesen, Ragnhild; Ossipova, Elena; Lundqvist, Christina; et al. (Frontiers in Immunology, 2019)
Rheumatoid arthritis (RA) associated anti-citrullinated protein autoantibodies (ACPA) target a wide range of modified proteins. Citrullination occurs during physiological processes such as apoptosis, yet little is known about the interaction of ACPA with nuclear antigens or apoptotic cells. Since uncleared apoptotic cells and neutrophil extracellular trap (NET) products have been postulated to be central sources of autoantigen and immunostimulation in autoimmune disease, we sought to characterize the anti-nuclear and anti-neutrophil reactivities of ACPA. Serology showed that a subset of anti-CCP2 seropositive RA patients had high reactivity to full-length citrullinated histones. In contrast, seronegative RA patients displayed elevated IgG reactivity to native histone compared to controls, but no citrulline-specific reactivity. Screening of ten single B-cell derived monoclonal ACPA from RA patients revealed that four ACPA exhibited strong binding to apoptotic cells and three of these had anti-nuclear (ANA) autoantibody reactivity. Modified histones were confirmed to be the primary targets of this anti-nuclear ACPA subset following immunoprecipitation from apoptotic cell lysates. Monoclonal ACPA were also screened for reactivities against stimulated murine and human neutrophils, and all the nuclear-reactive monoclonal ACPA bound to NETs. Intriguingly, one ACPA mAb displayed a contrasting cytoplasmic perinuclear neutrophil binding and may represent a different NET-reactive ACPA subset. Notably, studies of CRISPR-Cas9 PAD4 KO cells and cells from PAD KO mice showed that the cytoplasmic NET-binding was fully dependent on PAD4, whilst nuclear- and histone-mediated NET reactivity was largely PAD-independent. Our further analysis revealed that the nuclear binding could be explained by consensus-motif driven ACPA cross-reactivity to acetylated histones. Specific acetylated histone peptides targeted by the monoclonal antibodies were identified and the anti-modified protein autoantibody (AMPA) profile of the ACPA was found to correlate with the functional activity of the antibodies. In conclusion, when investigating monoclonal ACPA, we could group ACPA into distinct subsets based on their nuclear binding-patterns and acetylation-mediated binding to apoptotic cells, neutrophils, and NETs. Differential anti-modified protein reactivities of RA-autoantibody subsets could have an important functional impact and provide insights in RA pathogenesis.